The Host Response in Tissue Engineering: Crosstalk Between Immune cells and Cell-laden Scaffolds - Saleh, Leila S. (Curr Opin Biomed Eng, 2018)
Implantation of cell-laden scaffolds is a promising strategy for regenerating tissue that has been damaged due to injury or disease. However, the act of implantation initiates an acute inflammatory response. If the scaffold is non-biologic (i.e., a modified biologic scaffold or synthetic-based scaffold), inflammation will be prolonged through the foreign body response (FBR), which eventually forms a fibrous capsule and walls off the implant from the surrounding host tissue. This host response, from a cellular perspective, can create a harsh environment leading to long-lasting effects on the tissue engineering outcome. At the same time, cells embedded within the scaffold can respond to this environment and influence the interrogating immune cells (e.g., macrophages). This crosstalk, depending on the type of cell, can dramatically influence the host response. This review provides an overview of the FBR and highlights important and recent advancements in the host response to cell-laden scaffolds with a focus on the impact of the communication between immune cells and cells embedded within a scaffold. Understanding this complex interplay between the immune cells, notably macrophages, and the tissue engineering cells is a critically important component to a successful in vivo tissue engineering therapy.